Struktur Histologi dan Histomorfometri Kulit Anjing Ras Kintamani Asal Bali - Kurniawati, Ni Made Ayu; Setiasih, Ni Luh Eka; Suastika, Putu (Jurnal Veteriner; Vol 21 No 4 (2020), 2020)
Kintamani dog is the only Balinese breed has been recognized by Federarion of International Cynology (Fédération Cynologique Internationale). Kintamani dogs live around Sukawana Village, Kintamani District, Bangli Regency, of Bali. The purpose of this study was to determine the hystologycal structure and histomorphometry of kintamani dog skin. The kintamani dog used in this study were 1-2 years old. Histological structure observed by carlzeiss teaching microscope with objective lens magnification 5, 10, 20, 40, and 100x. In this study, the hystologycal structure of kintamani dog consists of the epidermis, dermis, and hypodermis, except on planum nasale. Planum nasale of kintamani dogs do not have hypodermis. The other components found in the hystologycal structure is sebaseous gland, sweat gland, hair follicles and blood vessels. While the histomorphometry of kintamani dog skin have a different thickness depending on location of the body and gender. In this study, Kintamani dog skin is the thickest in female planum nasale with thickness from epidermis to dermis at 6437.040 ?m and the thinnest in male stomach at 2047.378 ?m.